UNDERSTANDING TAX AVOIDANCE : INSIGHTS FROM COMMISSIONERS, OWNERSHIP, AUDIT, EXECUTIVES - Michael, Michael; Widjaja, William (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study looks at the impact of institutional ownership, independent commissioners, external audits, and executive personality on tax avoidance in the Indonesian food and beverage industry. The findings demonstrate that independent commissioners significantly reduce the incidence of tax evasion. Analyzing 60 financial reports spanning 2018 to 2022, it finds that independent commissioners significantly decrease tax avoidance, highlighting the importance of internal oversight for transparency. However, institutional ownership, external audit, and executive character show no significant impact. These results underscore the intricate nature of tax avoidance and advocate for a comprehensive supervisory framework to manage tax risks and uphold corporate reputation effectively. The research contributes valuable insights into corporate governance and tax compliance, offering practical guidance for practitioners to enhance transparency and integrity within their organizations. Ultimately, these efforts aim to improve tax compliance and reputation management in the food and beverage sector.